Determinants of Generation Z Behavior in Zakat, Infaq and Shodaqoh (ZIS) Payments: The Role of Sharia Financial Literacy Mediation - Lintang Kurniawati; Indah Permata Dewi; Nur Kholis (LPPM ISNJ Bengkalis, 2026)
Purpose – analyze individual factors that influence generation Z in paying zakat, infak and shodaqoh (ZIS) with digital platforms mediated by sharia financial literacy. Method – This study is a quantitative research using primary data from the distribution of questionnaires. The population used was students in Central Java and D.I Yogyakarta using purposive sampling. The analysis method used SEM-PLS (structural Equation Modelling-Partial Least Square) analysis with the SMARTPLS analysis tool version 4.0. This study uses independent variables of intellectual intelligence, fintech, and religiosity. The mediation variable uses Islamic financial literacy. Meanwhile, the dependent variable is zakat payments with digital platforms. Findings – The results of this study found that the variables of financial technology (Fintech) and religiosity had a direct effect on ZIS payments with digital platforms, but the intellectual intelligence variables did not have a direct effect on ZIS payments with digital platforms. Meanwhile, the sharia financial literacy variable is able to mediate the relationship between intellectual intelligence, fintech, and religiosity to ZIS payments with digital platforms. Implications – provides implications for online zakat payment service providers to improve the image and credibility of their companies in maintaining reputation, developing service quality, innovating and providing the best service for the community.